DUKUNGAN SOSIAL DAN PERILAKU PERAWATAN DIRI PENYANDANG DIABETES MELITUS TIPE 2 - EMILIA ERNINGWATI AKOIT (JURNAL INFO KESEHATAN, 2015)
The success of self - care behaviors in type 2 diabetes Mellitus patients influenced by various factors, one of them is social support. This study aims to identify the relationship between social support and self-care behavior in type 2 diabetes patients. This research used cross-sectional design, recruited 112 type 2diabetes patients in Hospital A in Jakarta. The questionnaire used in this study including Social Support for Self Care in Middle-Aged Diabetes (S4-MAD), Summary Diabetes Self Care Activity (SDSCA), Diabetes Knowledge (DKN) Scale dan The Diabetes Management Self Efficacy Scale (DMSES. The result showed there was the significant correlation between social support and self-care behavior (p-value=0.002). Multivariate analysis showed social support was the most predictor after controlling by self-efficacy (p-value = 0.004). Improving social support can be achieved by involving family member as the support system. Additionally, encouraging type 2 diabetes patients joined up in the social group (PERSADIA), could be better since they gain more information about diabetes will result in improved self.